The role of culture in English language teaching - Pastor Gaspar, Tania Judith (2021)
Starting from the premise that every source of knowledge resides in the experience that the subject has of the world, in this research I decided to reflect on the cultural representations with which the university student begins the learning of a foreign language. Culture finds expression in language; then, learning a new language without familiarity with its culture remains incomplete. Here an important question arises: is it necessary to learn about the culture of the target language in order to acquire English as a foreign language? There are great discussions of many academics and researchers on this topic for decades. This research aims to define the culture, its relationship with language and what role it plays in the teaching of English as a foreign language. The corpus obtained from the responses of the students to a brief survey, allows me to identify the images that circulate in our classes about the culture of the main English-speaking countries with respect to the local culture. I propose to observe how the presence of this imaginary allows (or not) to evolve representations and images about the language and culture studied.